1989
DOI: 10.1016/0014-5793(89)81068-3
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan decarboxylase from Catharanthus roseus is a pyridoxoquinoprotein

Abstract: Tryptophan decarboxylase (EC 4.1.1.28) from Catharanthus roseus was purified to homogeneity. The native enzyme has an M r of about 96000 as estimated from native PAGE. After SDS‐PAGE, three protein bands were visible corresponding with M r 49000, 33000 and 17000. The N‐termini of the 49 kDa protein and the 33 kDa protein were identical. Antibodies against the 49 kDA protein also reacted strongly with the two smaller proteins. It is concluded that the native enzyme consists of two subunits of M r 49000. Tryptop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…This enzyme was purified first by Noe and Berlin (1984), later this protein was extensively characterized (Fernandez et al 1989;Pennings et al 1989a, b). The enzyme is a soluble protein consisting of two identical subunits containing two molecules of pyridoxal phosphate (Pennings et al 1989a). It was observed that TDC activity can be induced when suspension cultures of C. roseus are transferred from growth medium to alkaloid induction medium that contains a high concentration of sugar and low levels of hormones, nitrogen and phosphate (Knobloch et al 1981).…”
Section: Biosynthesis Of Tryptaminementioning
confidence: 97%
See 1 more Smart Citation
“…This enzyme was purified first by Noe and Berlin (1984), later this protein was extensively characterized (Fernandez et al 1989;Pennings et al 1989a, b). The enzyme is a soluble protein consisting of two identical subunits containing two molecules of pyridoxal phosphate (Pennings et al 1989a). It was observed that TDC activity can be induced when suspension cultures of C. roseus are transferred from growth medium to alkaloid induction medium that contains a high concentration of sugar and low levels of hormones, nitrogen and phosphate (Knobloch et al 1981).…”
Section: Biosynthesis Of Tryptaminementioning
confidence: 97%
“…4.1.1.28). This enzyme was purified first by Noe and Berlin (1984), later this protein was extensively characterized (Fernandez et al 1989;Pennings et al 1989a, b). The enzyme is a soluble protein consisting of two identical subunits containing two molecules of pyridoxal phosphate (Pennings et al 1989a).…”
Section: Biosynthesis Of Tryptaminementioning
confidence: 99%
“…In the following narrative, a small sample of specialized pathways is given to illustrate systems where future details of compartmenta tion or other spatial organization of catalytic domains can be anticipated. alkaloid synthesis in plants such as Catharanthus roseus, is a pyridoxo quinoprotein (91). In cases where a high output of indole alkaloids occurs, an understanding of the following aspects is essential: (a) the energy-drain impact of hyperutilization of a quantitatively minor amino acid that requires more energy input for biosynthesis than any of the protein amino acids; (b) the nature of cross-pathway relationships with respect to the role of tyrosine as a precursor of the pyrroloquinoline quinone cofactor needed for tryptophan decarboxylase; and (c) the spatial and metabolic relationship to the pathway of auxin synthesis, which also utilizes tryptophan as the starting precursor.…”
Section: Other Specialized Pathwaysmentioning
confidence: 99%
“…2) [for review see Kutchan (1993)]. It consists of two identical subunits containing two molecules of pyridoxal phosphate (Pennings et al 1989a). TDC has been isolated and purified from suspension cultures to apparent homogeneity (Pennings et al 1989b).…”
Section: Biosynthesis Enzymology and Regulationmentioning
confidence: 99%